Assembling an innovative social housing project in Melbourne: mapping the potential for social innovation. Issue 8 (14th September 2019) - Raynor, Katrina
Abstract: In Australia, echoing trends in the UK, US and Canada, provision of social housing has transitioned from government-led mechanisms to an increasing focus on partnerships between private developers, government and the not-for-profit sector. In this context, social housing is often achieved via the 'cobbling together' of necessary resources over time. This article focuses on an innovative social housing project in the inner west of Melbourne, Australia, that involves the modular construction of 57 transportable dwellings located on government-owned land. I apply a theoretical framework that combines insights from social innovation literature and assemblage to understand the process of assembling a pilot project and to chart how the project may be scaled up or scaled out to challenge the system in which homelessness occurs. The research highlights the role of community housing providers as 'pivot points' in the social housing sector and acknowledges the importance of credibility, funding, legislative change and construction innovation in scaling housing social innovations.